2017
DOI: 10.18203/2394-6040.ijcmph20174238
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its association with psychosocial factors among old age home inmates in an urban area of Kancheepuram district, Tamil Nadu

Abstract: Background: Among the non-communicable diseases prevalent among old age home inmates, hypertension is one of the diseases which if not diagnosed and treated adequately, could lead to high mortality and morbidity due to limited resources. The objective of this study is to find out the prevalence of hypertension among the old age home inmates and also its association with psychosocial morbidity among them. Methods: This community based cross sectional descriptive study was done among 250 inmates of selected old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The outcomes of the study also revealed that according to most of the respondents more than 50 percent think that weight loss is the best way to control hypertension the same was concluded by the study prevailed in Karachi and most of the respondents were aware of the fact that smoking is injurious for the hypertensive patient but it contradicts with the study conducted in Karachi which shows that people are least aware of it but at the same time the study in Karachi reveals that exercise, reduce salt intake also controls blood pressure which satisfies the study conducted in Bahawalpur which shows the same results (19). The study also showed that the majority of the population more than fifty percent thinks that lifestyle modifications are important to control hypertension and the same was observed from the study conducted in China which showed that the majority of the population has the same thinking (29). This study showed that more than 50 percent that is in majority of the respondents believe that alcohol should be avoided by people who are suffering from hypertension on the other hand very few of the respondents did not support this statement and according to them quitting alcohol is not important for the people suffering from hypertension.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The outcomes of the study also revealed that according to most of the respondents more than 50 percent think that weight loss is the best way to control hypertension the same was concluded by the study prevailed in Karachi and most of the respondents were aware of the fact that smoking is injurious for the hypertensive patient but it contradicts with the study conducted in Karachi which shows that people are least aware of it but at the same time the study in Karachi reveals that exercise, reduce salt intake also controls blood pressure which satisfies the study conducted in Bahawalpur which shows the same results (19). The study also showed that the majority of the population more than fifty percent thinks that lifestyle modifications are important to control hypertension and the same was observed from the study conducted in China which showed that the majority of the population has the same thinking (29). This study showed that more than 50 percent that is in majority of the respondents believe that alcohol should be avoided by people who are suffering from hypertension on the other hand very few of the respondents did not support this statement and according to them quitting alcohol is not important for the people suffering from hypertension.…”
Section: Discussionsupporting
confidence: 68%
“…It showed that illiterate people have poor knowledge and awareness of hypertension. It is also manifested that the awareness of hypertension among the people of Bahawalpur is greater as compared to the population of China (29). The factor of age is also responsible for susceptibility to the patient of hypertension.…”
Section: Discussionmentioning
confidence: 99%